Challenges and Opportunities in Implementation of Future California Rail Network. Issue 1 (2016) - Levy, Samuel; Faulkner, A. Awadagin; Sussman, Joseph M.
The California High-Speed Rail Authority adopted a blended system at the northern and southern terminuses of the planned first phase of its high-speed rail line. In this blended operation, the high-speed rail line share track and other infrastructure with commuter, intercity, and freight rail. However, the lack of common infrastructure between rail modes and the financial and organizational challenges associated with building that common infrastructure and capacity allocation in California present challenges for the implementation of high-speed rail by a blended system in the state. This paper reviews the blended system and discusses the level of cooperation and coordination necessary between host railroads–agencies and the operator of the high-speed rail tenant. Sharing track comes with challenges for all participating railroad operators and often requires coordination between heterogeneous rail traffic. However, costs can be reduced when compared with those for dedicated track. How blended service is performed will affect state and local agencies, railroad owners and operators, and customers across the California rail network.